THE EFFECT OF STAKEHOLDERS’ PRESSURE AND CORPORATE FINANCIAL PERFORMANCE ON TRANSPARENCY OF SUSTAINABILITY REPORT - Yuana Jatu Nilawati; Elis Purwanti; Fithri Alvionita Nuryaman (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
The purpose of this research is to investigate the effect of stakeholder’s pressure and corporate financial performance on transparency of sustainabilty report. The population of this research comprises as State-owned Enterprise (SOE) listed on Indonesia Stock Exchange (IDX) during years 2013-2017. The technique of determining the sample used purposive sampling. This research uses a multiple linear regression. Form this research, proved that environmental sensitive industry, investor oriented industry, and corporate financial performance have effect simultaneously toward transparency of sustainabilty report. This research also proved that partially environmental sensitive industry, investor oriented industry, and corporate financial performance have positive effect toward transparency of sustainabilty report.